2019
DOI: 10.5005/jp-journals-10071-23148
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Agents-induced Hypokalemia: A Possible Causality Association

Abstract: Background Drugs including some of the antimicrobial agents (AMAs) can cause mild to severe intensity of hypokalemia, which leads to cardiac, muscular, renal, gastrointestinal, and metabolic manifestations. Objective To explore the possible association of AMAs use and the development of hypokalemia as an adverse drug reaction (ADR). Methodology Retrospective analysis of spontaneously individual case safety reports (ICSRs) received during Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…However, there was a significant reduction in the metabolic hydrogen ions between the concentrate without probiotics or antibiotics group and the group that received concentrate with antibiotics. Medications, including antibiotics, may cause hypokalemia, which may lead to metabolic alkalosis [34]. Therefore, the ABB is a useful physiological stress indicator in farm animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a significant reduction in the metabolic hydrogen ions between the concentrate without probiotics or antibiotics group and the group that received concentrate with antibiotics. Medications, including antibiotics, may cause hypokalemia, which may lead to metabolic alkalosis [34]. Therefore, the ABB is a useful physiological stress indicator in farm animals.…”
Section: Discussionmentioning
confidence: 99%
“…27 The co-administration of ceftriaxone and furosemide has a hypokalemic effect, and prolonged use of proton pump inhibitors with furosemide can lead to hypomagnesemiarelated fluid and electrolyte imbalances, which should not be overlooked. 28 A point-prevalence study conducted in a Turkish pediatric clinic to investigate the prevalence of inappropriate drug use reported that clarithromycin and ceftriaxone were the most commonly used antibiotics. 21 Although not examined in this study, considering the rates of potential interaction risks, further studies on the necessity of using these two drugs could be the subject of another research endeavor.…”
Section: Discussionmentioning
confidence: 99%
“…21 We had a similar number of patients using 15 different antibiotics, three antivirals, two antifungals, three antiparasitic agents, and one antituberculous drug along with a miscellaneous group, many of which have been associated with hypokalemia. Other antimicrobials that have been reported to cause or be associated with hypokalemia are cyclosporine, 29 fluconazole, 30 acyclovir, 31 azithromycin, 32 ceftriaxone, 32 ampicillin, 18 rifampicin, 21 colistin, 33 clindamycin, 14 meropenem, 34 ciprofloxacin, 21 and entecavir. 35 Other drugs in hospitalized patients include thyroxine, 36 thiamine, 37 vitamin B12, 38 imatinib, 39 hydroxychloroquine, 40 valproate, 41 and noradrenaline.…”
Section: Discussionmentioning
confidence: 99%